Provision of technical protection of the railroads in crisis situations by the private construction companies - Viskup, Pavel; Soušek, Radovan; Šustr, Martin (International Institute of Informatics and Systematic, 2017)
After 1989 became changes in the Czechoslovakia (Czech Republic). The Crisis management in the railway transport can’t stay. In the recent years is a necessary new system for effectivity and economic profitability.
Technická ochrana a obnova železniční sítě v krizových situacích zabezpečená soukromopravními stavebními organizacemi
Keywords: technical protection; crisis situations; renewal of railways; civil organizations; technická ochrana; krizová situace; obnova železniční sítě; soukromoprávní organizace